2008
DOI: 10.1186/1471-2466-8-16
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia and hospital outcomes among patients with pneumonia: a retrospective cohort study

Abstract: Background: Community-acquired (CAP) and nosocomial pneumonias contribute substantially to morbidity and hospital resource utilization. Hyponatremia, occurring in >1/4 of patients with CAP, is associated with greater disease severity and worsened outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
94
2
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 25 publications
8
94
2
7
Order By: Relevance
“…16 Likewise, a study by Zilberberg and colleagues reported no significant increased risk of death with hyponatremia compared with normonatremia. 4 These results are similar to our results for all-cause hyponatremia and for hyponatremia subgrouped by severity. In contrast, a study by Nair and colleagues reported some increased risk of death with hyponatremia.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…16 Likewise, a study by Zilberberg and colleagues reported no significant increased risk of death with hyponatremia compared with normonatremia. 4 These results are similar to our results for all-cause hyponatremia and for hyponatremia subgrouped by severity. In contrast, a study by Nair and colleagues reported some increased risk of death with hyponatremia.…”
Section: Discussionsupporting
confidence: 82%
“…2 Previous studies have suggested that the presence and degree of hyponatremia is associated with the severity of pneumonia in adults and children, although the results have differed among studies. [3][4][5][6][7] Hyponatremia is caused by various factors, including volume depletion, use of diuretics, hypothyroidism, adrenal insufficiency, heart failure, renal failure, and cirrhosis. Additionally, the syndrome of inappropriate antidiuresis (SIAD) is a frequent and heterogeneous disorder characterized by hyponatremia and impaired urinary dilution in the absence of any recognized stimulation of antidiuretic hormone secretion.…”
mentioning
confidence: 99%
“…In the study by Zilberberg et al, the frequency of hyponatraemia that accompanies community acquired pneumonia was estimated at 8.1%. They observed longer hospital stays in these patients, higher frequency of hospitalization in intensive care units, and mechanical ventilation [16]. However, no statistically significant difference was found (similarly as in the previously mentioned studies by Waikar et al [11]) in the frequency of in-hospital deaths in these patients.…”
Section: Discussioncontrasting
confidence: 36%
“…34 Zilberberg et al reported that hyponatremia was associated with increased mortality. 35 We did not find any significant effect of laboratory parameters (Na, BUN, albumin, creatinine, hemoglobin, WBC and CRP) on mortality.…”
mentioning
confidence: 73%